Решить неравенства: -2)(6-x)(4x+1)< 0 2) (1-2x)(2x-3)(5x-2)< 0 -3)(x-1)x(5x-4)< 0 -2)(1-x)(5x+2)> 0 можно написать просто ответ

annakrasnikova2 annakrasnikova2    3   02.08.2019 01:10    0

Ответы
1АндрейKEK 1АндрейKEK  08.09.2020 01:58
1)(-3x-2)(6-x)(4x+1)<0
(3x+2)(x-6)(4x+1)<0
x=-2/3  x=6  x=-1/4
            _               +                  _                +
(-2/3)(-1/4)(6)
x∈(-∞;-2/3) U (-1/4;6)
-
2) (1-2x)(2x-3)(5x-2)<0
x=0,5      x=1,5  x=0,4
       +                _                +                _
(0,4)(0,5)(1,5)
x∈(0,4;0,5) U (1,5;∞)

3)(-2x-3)(x-1)x(5x-4)<0
(2x+3)(x-1)x(5x-4)>0
x=-1,5  x=1  x=0  x=0,8
         +                  _                  +                _                    +
(-1,5)(0)(0,8)(1)
x∈(-∞;-1,5) U (0;0,8) U (1;∞)

4)(-x-2)(1-x)(5x+2)>0
(x+2)(x-1)x(5x+2)>0
x=-2  x=1  x=0  x=-0,4
+                  _                  +                _                    +
(-2)(-0,4)(0)(1)
x∈(-∞;-2) U (-0,4;0) U (1;∞)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра